Political discourse analysis: spin-doctoring paradigm - Kovalevska, Anastasia (Current issues of Ukrainian linguistics: theory and practice, 2020)
The author of the article analyzes the realization of verbal influence (also known as suggestion) phenomenon in political discourse, which is defined as a whole combined image of the text itself and emotions of its recipient and addressee,including the peculiarities of perception, external and internal circumstances, its pragmatic and linguistic aspects, etc, and is aimed at a a political subject’s (politics, political force, power) influencing a political object (audience, electorate, voter). Most scientists study political discourse and its immanent influential properties from the standpoint of Psychology, Communicative Linguistics, Pragmalinguistics, Political :inguistics and other related sciences, but the author proposes to research the peculiarities of perception, processing and generation of information and its transformations from deep thought structures to superficial speech with the help of involving Neurolinguistic Programming as a modern science which deals with analyzing such concepts; as well as Spin-Doctoring, an ultramodern complex discipline aimed at a correction of the negative gestalted image of the event in the media after its has already happened or right before its manifestation, which is impossible without the involvement of language techniques to influence the recipient or group of recipients. In order to fully research the political discourse, which in the network of this article is represented by the political speeches of the leaders of Ukraine, USA, France, Spain, Italy, Canada, Germany, the author involves both the basic techniques of political discourse correction which are utilized in Spin-Doctoring ( negative information delay, ambiguous informing, focus switch, interspersing the artificial situations with elements of naturalness, and the technique of controlled information leaks and preparation for events expectations); and the meta- and Milton-model analysis of the text hving been researched and developed in the NLP paradigm in order to isolate the actual linguistic influential patterns (markers of language metamodeling processes, simple, complex and indirect inductions). The analysis details the available data on the peculiarities of the implementing and enhancing the linguistic influence within the political discourse, as well as outlines the next steps in the development of research dedicated to this phenomenon.
Keywords: political discourse, Spin-Doctoring, Neurolinguistic Programming, NLP, language influence, suggestion, language metamodel, Milton-model of language, suggestive text, politics, discourse, techniques of influence.